HYGIENIC ASSESSMENT OF THE NUTRITIONAL STATUS OF PATIENTS WITH ORAL CANCER (World Bulletin of Public Health, 2025)
According to the assessment of the nutritional status of patients with oral cavity cancer (OCC), the average number of meals per day was 3.5 ± 0.1. By type of nutrition: 40 patients (85.1%) had natural (oral) feeding, 5 (10.6%) mixed (combined), and 2 (4.2%) enteral feeding. In 40.0% of patients, meat and meat products; in 50.0%, grains and cereals; in 37.0%, vegetables and gourds; in 17.0%, fruits; in 52.0%, legumes; and in 37.0%, milk and dairy products were consumed below physiological norms. The following were consumed above physiological norms: 15.0% confectionery products, 55.0% bread and high-grade flour products, 60.0% fast food and processed products, 20.0% chemically processed products, 12.0% spicy and salty foods, and 17.0% carbonated and colored drinks. This may reduce immune system function and increase the risk of cancer development and complications
Keywords: Oral cavity cancer; nutrition; products